Republic of Moldova : Financial Sector Assessment Program-Oversight and Supervision of Financial Market Infrastructures (FMIS) and Risk Assessment of Central Securities Depositories-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
Moldova has a modern interbank payment system that lies at the heart of its financial markets. The Automated Interbank Payment System (AIPS) settled on average MDL 2 billion (USD 214 million) per day, or 2.7 percent of GDP in 2013. It has real-time gross settlement features that help reduce systemic risks, settles large-value and time-critical payments, and is interdependent with two securities settlement systems. This includes the central bank's Book-Entry System (BES) that handles government securities and central bank certificate settlements, and the National Securities Depository (NSD) that settles private sector securities trades. It largely met international standards in the FSAP Update of 2008. A self-assessment of the BES against the CPSS-IOSCO Principles for Financial Market Infrastructures (PFMIs) has been completed in December 2013 by the NBM. The preliminary results suggest full observance with 11 principles and broad observance with three principles (Principle 1 on Legal Basis, Principle 22 on Communication Procedures and Standards). They are currently under the peer review process by the National Commission for Financial Markets (NCFM).